2014
DOI: 10.1155/2014/580264
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea, Excessive Daytime Sleepiness, and Road Traffic Accidents among Interstate Commercial Vehicle Drivers in Nigeria

Abstract: Introduction. Obstructive sleep apnea (OSA) is a growing public health problem in developing countries. However the burden among commercial drivers is not well described. Methods. The Epworth Sleepiness Scale (ESS) and Berlin questionnaire were administered to interstate commercial road transport drivers to assess the tendency to sleep in daytime and the risk of OSA, respectively. Body mass index (BMI), neck, and waist-hip circumferences were measured. Results. Out of 138 commercial drivers, 124 (90%) responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Neck circumference has a positive correlation with Mallampati scores as found in this study. [8,9]. However, the correlation between other possible predictors of obstructive sleep apnoea such as age, sex, blood glucose, blood pressure were not considered in this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Neck circumference has a positive correlation with Mallampati scores as found in this study. [8,9]. However, the correlation between other possible predictors of obstructive sleep apnoea such as age, sex, blood glucose, blood pressure were not considered in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Screening for Obstructive sleep apnoea in drivers is very important as undiagnosed cases among them poses risk for the society due to their job. Several studies in Nigeria have shown that commercial car drivers are particularly at risk of Obstructive sleep apnoea [8][9][10]. However, these studies did not consider the relationship between these obesity indices.…”
Section: Introductionmentioning
confidence: 99%